2005
DOI: 10.1097/01.ccm.0000189943.60945.77
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of myocardial hibernation in the septic heart*

Abstract: Sepsis-associated cardiac dysfunction may reflect hibernation. Furthermore, such down-regulation of cellular function may underlie sepsis-induced dysfunction in other organ systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(93 citation statements)
references
References 29 publications
7
79
1
4
Order By: Relevance
“…This is consistent with other studies documenting myocardial depression in sepsis in both animal models [23] and humans [24,25]. By 24 h, when sepsis had become established, haemodynamic function had improved, despite persisting hyperlactataemia and a marked increase in clinical severity.…”
Section: Discussionsupporting
confidence: 80%
“…This is consistent with other studies documenting myocardial depression in sepsis in both animal models [23] and humans [24,25]. By 24 h, when sepsis had become established, haemodynamic function had improved, despite persisting hyperlactataemia and a marked increase in clinical severity.…”
Section: Discussionsupporting
confidence: 80%
“…Hypothermia and reduced metabolism, the hallmarks of hibernation, are frequently seen in experimental sepsis and in septic neonates (50,51,52). Furthermore, evidence of myocardial hibernation has recently been demonstrated in the septic heart in the absence of ischemia or hypoxia (38).…”
Section: Metabolic Down-regulation and Hibernationmentioning
confidence: 99%
“…Sepsis is one disease process in which cellular hibernation has been proposed to underlie organ failure (2,38,49). During sepsis, there is often profound organ dysfunction with histologic absence of injury and minimal cell death (49).…”
Section: Metabolic Down-regulation and Hibernationmentioning
confidence: 99%
“…In a previous study, we have demonstrated that sepsis also causes diastolic dysfunction associated with an, increase in both the left ventricular filling pressure (LVEDP) and the rate constant (tau) for left ventricular relaxation time during hyperdynamic state of sepsis (1-day post-sepsis) (Chopra and Sharma, 2007). Other investigators have also provided evidence for altered cardiodynamic responses in both animal and clinical models of sepsis (Brahmbhatt et al, 2005;Levy et al, 2005;Meldrum et al, 2005;Sharma, 2007).…”
Section: Introductionmentioning
confidence: 92%